The impact of leader-member exchange differentiation on team effectiveness among Malaysian nurses: team potency as mediator - Azizan, Farah Lina; Darus, Amer; Othman, Noraini (2017)
This study examines how Malaysian leader and member in healthcare industry interpret and demonstrate leader-member relationships differentiation influence team effectiveness, operationalized as team satisfaction and team viability. Our sample of 475 staff nurses represented 92 wards in four hospitals. Results revealed that team potency mediates the relationship between LMX differentiation and team effectiveness. These findings validate our proposition of leader-member exchange differentiation in Malaysian healthcare industry and empirical support for the central roles of team potency as a socio-emotional process in workgroups.